Whole Exome Sequencing Confirms Molecular Diagnostics of Three Pakhtun Families With Autosomal Recessive Epidermolysis Bullosa - Fozia, Fozia; Nazli, Rubina; Bibi, Nousheen; Khan, Sher Alam; Muhammad, Noor; Shakeeb, Nafila; Khan, Saadullah; Jelani, Musharraf; Wasif, Naveed (Frontiers in Pediatrics, 2021)
Epidermolysis bullosa (EB) is a genetic skin disorder that shows heterogeneous clinical fragility. The patients develop skin blisters congenitally or in the early years of life at the dermo-epithelial junctions, including erosions, hyperkeratosis over the palms and soles. The other associated features are hypotrichosis on the scalp, absent or dystrophic nails, and dental anomalies. Molecular diagnosis through whole-exome sequencing (WES) has become one of the successful tool in clinical setups. In this study, three Pakhtun families from the Khyber Pakhtunkhwa province of Pakistan were ascertained. WES analysis of a proband in each family revealed two novel variants (COL17A1: NM_000494.4: c.4041T>G: p.Y1347* and PLEC: NM_201380.3: c.1283_1285delGCT: p.L426del) and one previously known COL17A1: NM_000494.4:c.3067C>T: p.Q1023*) variant in homozygous forms. Sanger sequencing of the identified variants confirmed that the heterozygous genotypes of the obligate carriers. The identified variants have not only increased the mutation spectrum of the COL17A1 and PLEC but also confirms their vital role in the morphogenesis of skin and its associated appendages. WES can be used as a first-line diagnostic tool in genetic testing and counselling families from Khyber Pakhtunkhwa, Pakistan.